Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/wrr.12789
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan‐calcium alginate dressing promotes wound healing: A preliminary study

Abstract: Dressings are necessary during the process of wound healing. Since the early 1980s, several types of wound dressings have been produced, but they cannot always take into account some effects include antibacterial effect, wound healing promotion, and other properties. In this study, we would like to develop an effective dressing with the above properties, especially accelerating wound healing effect. A chitosancalcium alginate dressing (CCAD) was developed by coating mixture of chitosan with high-low molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 38 publications
1
47
0
1
Order By: Relevance
“…Angiogenesis is another important step of wound healing, which can provide necessary nutrition for granulation and surrounding tissues. [ 42,43 ] As mentioned before, angiogenesis was initiated promptly in the USCS group compared with controls, and the potential mechanism was also discussed in this work. Previous studies have shown that the expression of endogenous vascular endothelial growth factor (VEGF) is significantly increased during wound‐healing angiogenesis, especially in the early stage of capillary formation; [ 44,45 ] thus, the time course of VEGF expression level was also determined by immuno‐histochemical analysis on days 3, 7, and 12 after wounding ( Figure 9 ).…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…Angiogenesis is another important step of wound healing, which can provide necessary nutrition for granulation and surrounding tissues. [ 42,43 ] As mentioned before, angiogenesis was initiated promptly in the USCS group compared with controls, and the potential mechanism was also discussed in this work. Previous studies have shown that the expression of endogenous vascular endothelial growth factor (VEGF) is significantly increased during wound‐healing angiogenesis, especially in the early stage of capillary formation; [ 44,45 ] thus, the time course of VEGF expression level was also determined by immuno‐histochemical analysis on days 3, 7, and 12 after wounding ( Figure 9 ).…”
Section: Resultsmentioning
confidence: 65%
“…These samples were fixed in 4% paraformaldehyde for at least 24 h, subsequently embedded in paraffin and sectioned into a thickness of 10 µm to undergo routine histological processing with hematoxylin–eosin and Masson's Trichrome staining for histological analysis. [ 24,30,42,46 ] Primary antibodies for CK10, VEGF (Abcam, Cambridge, MA), and SP‐POD kit (Solarbio Science & Technology Co., Ltd.) for immuno‐histochemistry analysis. [ 30,42,44 ] Antigen retrieval was performed on sections under heating, and then incubation with a blocking reagent for 20 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, high MW chitosan (>100,000 Da) inhibits the growth of Gram-positive bacteria and regulates complement-mediated activities [ 39 , 40 ]. In our previous study, we have optimized the properties of chitosan by using a mixture of high MW and low MW forms [ 41 ]. However, chitosan solutions are viscous; dressings prepared with chitosan solution alone will adhere to the wound and promote tears in the granulation tissue during dressing changes that are not conducive to wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, considerable advances have been achieved in designing modern dressings to protect the wound from dehydration and infection, and facilitate the healing process instead of just covering the wound [3,11,12]. Wound dressings in the form of hydrogels [13][14][15], hydrocolloids [16][17][18], sponges [19][20][21][22], alginates [23][24][25], and transparent films [11] have been developed and some of them are commercially available. These materials are different in their inherent features, such as hydrophobicity, permeability, and adsorption capacity.…”
Section: Introductionmentioning
confidence: 99%